Nitrogen phosphorous derived carbons from Peltophorum pterocarpum leaves as anodes for lead–carbon hybrid ultracapacitors. (June 2020) - Muduli, Sadananda; Rotte, Naresh K.; Naresh, Vangapally; Martha, Surendra K.
Highlights: NPC synthesized from Peltophorum pterocarpum leaves using H3 PO4 at 550 °C. NPC exhibit capacitance of 640 F g −1 at a current density of 10 Ag −1 . PbCHUC delivers capacitance retention of >95% for about 15, 000 cycles at 5 Ag −1 . P doping partially modifies the electronic state of the carbon and NPC is pseudocapacitive in nature. Abstract: Lead–carbon hybrid ultra-capacitors are emerging as an alternative to a lead-acid battery, owing to the absence of sulfation, thereby enhancing cycle life and C rate performances. In this work, Nitrogen and Phosphorous derived carbons are synthesized from the Peltophorum pterocarpum leaves by treating with phosphoric acid followed by carbonization at 550 °C for 3 hrs. These carbons contain about 3.76% of Nitrogen and 1.26% of Phosphorous and have a BET surface area of 443 m 2 g −1 . Specific capacitances of 1032 F g −1 and 640 F g −1 at current densities of 1 A g −1 and 10 A g −1, respectively in 4.5 M. sulfuric acid are achieved for these carbon-based electrodes. The hybrid ultra-capacitor fabricated by using PbO2 positive electrode and Nitrogen and Phosphorous derived carbons coated on to graphite sheet as a negative electrode shows cycling stability with capacitance retention of >95% for about 15, 000 cycles at an applied current density of 5 A g −1 . The pseudocapacitive nature of as-synthesized carbon exhibits significant improvement in electrochemical performance in lead–carbon ultra-capacitors. Graphical abstract: Pb–C hybrid ultra capacitor using NPC-carbons as negative active material synthesized from Peltophorum pterocarpum leaves Image, graphical abstract